A study on recruitment and selection process for achieving higher employee productivity of IDLC Finance Limited. - Juthi, Manoka Jalil (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.